Utilization of Post-Coal Mining Reclaimed Land for Livestock Feed and Animal Husbandry Production: Challenges of Microbial Contamination, Heavy Metals, and Nutrient Deficiency - Budi Utomo; Aan Awaludin; Niati Ningsih; Dyah Laksito Rukmi; Wendy Triadji Nugroho; Anifiatiningrum Anifiatiningrum (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2026)
Coal mining causes significant environmental degradation, transforming land from a stable ecosystem into a disturbed area with complex ecological and chemical challenges. This study aims to evaluate the feasibility of post-coal mining reclaimed land as an area for livestock feed and animal husbandry production, focusing on the main research question: Does the land meet specific criteria such as heavy metal thresholds (e.g., Pb <0.3 mg/kg, Cd <0.1 mg/kg according to FAO/WHO), microbial community recovery (enzyme activity >30% increase), and nutrient availability (N, P, K >1% total)? The systematic literature review method involved searching 94 empirical articles from Google Scholar (years 2016-2025), selected based on criteria: empirical research design, English or Indonesian language, complete text, and relevance to the theme of mine land reclamation. Data analysis used a thematic approach to identify main themes related to reclaimed land conditions. The results show that 80% of studies report heavy metal pollution with Pb concentrations ranging from 5-50 mg/kg, Cd 0.5-5 mg/kg, and Hg 0.1-2 mg/kg, which pose a risk of bioaccumulation in feed plants; post-reclamation soil quality improvement trends reach 20-50% for soil organic carbon (SOC) and 30-60% for microbial enzyme activity, although the main constraints are slow microbial community recovery and chronic nutrient deficiency. In conclusion, reclaimed land is conditionally suitable for livestock feed and animal husbandry production if integrated restoration strategies are implemented to address microbial contamination, heavy metals, and nutrients, as well as continuous monitoring to ensure feed safety and animal health.